OPTIMALISASI PERAN BADAN PENASEHATAN, PEMBINAAN DAN PELESTARIAN PERKAWINAN (BP4) DALAM RANGKA PEMBENTUKAN KELUARGA SAKINAH DI KECAMATAN SEJANGKUNG KABUPATEN SAMBAS - Nazarudin Nazarudin; La Ode Ismail (Samawa (Sakinah, Mawaddah Warahmah), 2023)
According to Law Number 1 of 1974 concerning Marriage, which illustrates that marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the Supreme God One. The complexity of family problems that often occur in the community requires BP4 to formulate a new strategy to solve various problems in the household. Based on the phenomenon above, this study seeks to describe the steps that must be taken by the Advisory Board in the community to demand that BP4 formulate a new strategy to solve these various household problems. This type of research is field research, using qualitative methods. Because in this study it is hoped that a thorough and systematic description of the facts related to the problems of divorce cases will be obtained as a research development study. The role of the Marriage Advisory, Development and Preservation Agency (BP4) of Sambas district in the mechanism for forming a sakinah family is carried out by the Marriage Advisory, Development and Preservation Agency (BP4) using several efforts, namely Preventive Efforts and Curative Efforts. Preventive efforts are made when the couple is not married. While Curative Efforts are carried out when the couple has married.